Laminate composites with multiple delaminations - Song, Hao. (2008)
Delamination buckling is a failure scenario that lessens the structural integrity of laminated composite structural members. In the present work an analytical model is studied for inhomogeneous clamped beams with through-the-width multiple delaminations, located arbitrarily in both the spanwise and thicknesswise directions. The beam is modeled as seven separate component segments, each analyzed as an Euler beam with the "free mode deformation" assumption. Boundary conditions, continuity conditions of the displacement, slope, moment, shear force, and additional axial force compatibility equations are used to generate a system of 37 linear, homogeneous algebraic equations. This system of equations governs the behavior of the delaminated beam when subjected to compressive loading.